Extension of the δ-Plus-SPH model for simulating Vortex-Induced-Vibration problems. (October 2019) - Sun, P.N.; Colagrossi, A.; Le Touzé, D.; Zhang, A.-M.
Abstract: In this paper, the Lagrangian particle method δ - P l u s -SPH model is used to solve a series of benchmark test-cases of vortex induced vibrations (VIV). An Adaptive Particle Refinement (APR) technique is adopted to resolve correctly the boundary layer regions of the moving bodies, and to de-refine the particles that are transported far away. Furthermore, a switch correction on the pressure forces term is adopted in the momentum equation to completely remove the occurrence of the so-called Tensile Instability that leads to the development of numerical cavitation in negative pressure regions. Because of the Lagrangian nature of the method, difficulties arise when intense vortex wakes, typically developed in VIV problems, cross the outflow boundary. To this purpose, a damping zone is also implemented close to the outlet to improve the numerical stability of the scheme. The fluid–structure coupling technique is based on ghost particles properly generated inside the solid bodies. The validation is performed against test-cases for which reference solutions are available in the literature. Within those test-cases challenging benchmarks involving small mass ratios, large-amplitude body motions and multi-body interactions have been selected. For all the benchmark test-cases the δ - P l u s -SPH results are in good agreement with the reference solutions, demonstrating the ability of this particle method in solving complex VIV problems.